(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In a variety of sectors, deregulation and global competition are pushing institutions to turn to quality in order to please their consumers. Hospitals around the world, like other sectors, are also aiming for higher quality in all their operating areas. A comprehensive quality management system that has long-term consistency is needed to establish quality in hospitals. This study was conducted at a teaching hospital in Pune City’s Operation Theatre Complex. The case study was used in the OT complex to analyse the contemporary QMS phenomenon. Via various sources, data was collected. In the three phases of QMS implementation, the behaviors of healthcare professionals during preoperative treatment were reported for a total of ninety general surgery patients. In order to determine the understanding of healthcare professionals relevant to general surgery OT, interview and survey data were collected on the causes of discrepancies in patient preoperative care procedures and factors responsible for the sustainable implementation of QMS. In order to clarify the causes of differences in per-operative care procedures, thematic review of interview data was conducted. The test was used to compare the behaviors of different phases of QMS. For the perception analysis of healthcare professionals, MANOVA and factor analysis were applied. Implementation of QMS is a very complex process but equally essential for the organization’s development. While it is affected by a variety of factors, no single factor is responsible for the survival of the QMS.